Analisis Organizacional Y Financiera Del Uso De Prácticas Sustentables En Empresas Industriales Del Municipio De Tulancingo De Bravo Perteneciente Al Estado De Hidalgo - Sergio Demetrio Polo Jiménez; Eleazar Villegas González; Tirso Javier Hernández Gracia; Danae Duana Ávila; Ma. Del Rosario García Velázquez (European Scientific Journal, ESJ, 2017)
The purpose of the present investigation is to identify those internal factors that influence the implementation of socially responsible practices (energy saving) in a sample of 5 industrial companies in the municipality of Tulancingo de Bravo, Hidalgo in 2016. To achieve the proposed objectives, an index similar to that proposed by Barrera et al. (2004), Sepúlveda et al. (2002); Vázquez et al. (2011); Céspedes (2011); Carrillo in (2014). The results of the application of the Kruskal-Wallis test, could allow us to affirm that the development of sustainable practices in the companies of the sample, are still far from those carried out in Europe.